Identification of an oxygen-responsive element in the 5'-flanking sequence of the rat cytosolic phosphoenolpyruvate carboxykinase-1 gene, modulating its glucagon-dependent activation. - Bratke, J (1999)
The glucagon-stimulated transcription of the cytosolic phosphoenolpyruvate carboxykinase-1 (PCK1) gene is mediated by cAMP and positively modulated by oxygen in primary hepatocytes. Rat hepatocytes were transfected with constructs containing the first 2500, 493 or 281 bp of the PCK1 5'-flanking region in front of the chloramphenicol acetyltransferase (CAT) reporter gene. With all three constructs glucagon induced CAT activity with decreasing efficiency maximally under arterial pO2 and to about 65% under venous pO2. Rat hepatocytes were then transfected with constructs containing the first 493 bp of the PCK1 5'-flanking region in front of the luciferase (LUC) reporter gene, which were block-mutated at the CRE1 (cAMP-response element-1; -93/-86), putative CRE2 (-146/-139), promoter element (P) 1 (-118/-104), P2 (-193/-181) or P4 (-291/-273) sites. Glucagon induced LUC activity strongly when the P1 and P2 sites were mutated and weakly when the P4 site was mutated; induction of the P1, P2 and P4 mutants was positively modulated by the pO2. Glucagon also induced LUC activity strongly when the putative CRE2 site was altered; however, induction of the CRE2 mutant was not modulated by the pO2. Glucagon did not induce LUC activity when the CRE1 site was modified. These experiments suggested that the CRE1 but not the putative CRE2 was an essential site necessary for the cAMP-mediated PCK1 gene activation by glucagon and that the putative CRE2 site was involved in the oxygen-dependent modulation of PCK1 gene activation. To confirm these conclusions rat hepatocytes were transfected with simian virus 40 (SV40)-promoter-driven LUC-gene constructs containing three CRE1 sequences (-95/-84), three CRE2 sequences (-148/-137) or three CRE1 sequences plus two CRE2 sequences of the PCK1 gene in front of the SV40 promoter. Glucagon induced LUC activity markedly when the CRE1, but not when the CRE2, sites were in front of the SV40-LUC gene; however, induction of the (CRE1)3SV40-LUC constructs was not modulated by the pO2. Glucagon also induced LUC activity very strongly when the CRE1 and CRE2 sites were combined; induction of the (CRE1)3(CRE2)2SV40-LUC constructs was positively modulated by the pO2. These findings corroborated that sequences of the putative CRE2 site were responsible for the modulation by oxygen of the CRE1-dependent induction by glucagon of PCK1 gene transcription.